Insights into the tissue repair features of MAIT cells - Gao, Mengge; Zhao, Xiaosu (Frontiers in Immunology, 2024)
Mucosa-associated invariant T (MAIT) cells are a subset of innate-like nonconventional T cells characterized by multifunctionality. In addition to their wellrecognized antimicrobial activity, increasing attention is being drawn towards their roles in tissue homeostasis and repair. However, the precise mechanisms underlying these functions remain incompletely understood and are still subject to ongoing exploration. Currently, it appears that the tissue localization of MAIT cells and the nature of the diseases or stimuli, whether acute or chronic, may induce a dynamic interplay between their pro-inflammatory and anti-inflammatory, or pathogenic and reparative functions. Therefore, elucidating the conditions and mechanisms of MAIT cells' reparative functions is crucial for fully maximizing their protective effects and advancing future MAIT-related therapies. In this review, we will comprehensively discuss the establishment and potential mechanisms of their tissue repair functions as well as the translational application prospects and current challenges in this field.